The impact of cell-free supernatants of Lactococcus lactis subsp. lactis strains on the tyramine formation of Lactobacillus and Lactiplantibacillus strains isolated from cheese and beer - Purevdorj, Khatantuul; Buňková, Leona; Dlabajová, Andrea; Čechová, Erika; Pachlová, Vendula; Buňka, František (Food microbiology, 2021)
Tyramine is one of the most toxic biogenic amines and it is produced commonly by lactic acid bacteria in fermented food products. In present study, we investigated the influence of selected nisin-producing Lactococcus lactis subsp. lactis strains and their cell-free supernatants (CFSs) on tyramine production by four Lactobacillus and two Lactiplantibacillus strains isolated from cheese and beer. Firstly, we examined the antimicrobial effect of the CFSs from twelve Lactococcus strains against tested tyramine producers by agar-well diffusion assay. Six Lactococcus strains whose CFSs showed the highest antimicrobial effect on tyramine producers were further studied. Secondly, we investigated the influence of the selected six Lactococcus strains and their respective CFSs on tyramine production by tested Lactobacillus and Lactiplantibacillus strains in MRS broth supplemented with 2 g.L-1 of l-tyrosine. Tyramine production was monitored by HPLC-UV. The tyramine formation of all tested Lactobacillus and Lactiplantibacillus strains was not detected in the presence of Lc. lactis subsp. lactis CCDM 71 and CCDM 702, and their CFSs. Moreover, the remainder of the investigated Lactococcus strains (CCDM 670, CCDM 686, CCDM 689 and CCDM 731) and their CFSs decreased tyramine production significantly (P < 0.05) - even suppressing it completely in some cases - in four of the six tested tyramine producing strains.
Keywords: antibakteriální látky; pivo; kultivační média; Lactobacillus; Culture Media; Beer; tyramin; Lactococcus lactis; Cheese; Chromatography, High Pressure Liquid; Tyramine; vysokoúčinná kapalinová chromatografie; Lactobacillaceae; sýr; Anti-Bacterial Agents